Rottenberg at Sixty-Five: In Honor of the 20th Anniversary of the Journal of Sports Economics. (August 2022) - Fort, Rodney
Sports economics is now 65 years old, since Rottenberg's "The Baseball Players' Labor Market". This milestone coincides with the 20 th anniversary of the Journal of Sports Economics . Rottenberg's two main offerings, the match outcome uncertainty hypothesis and the invariance principle, are reviewed, including empirical verdicts from other recent literature reviews. In addition, perhaps less well-known issues in the literature suggest further investigation of these crucial hypotheses, and others that arise. Finally, the place of the Journal of Sports Economics in the evolution of sports economics is offered.